2011
DOI: 10.1016/j.bcp.2011.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Plant lectins are novel Toll-like receptor agonists

Abstract: The T cell mitogen and plant glycoprotein, phytohaemagglutinin (PHA), is commonly used to stimulate peripheral blood mononuclear cell (PBMC) preparations to produce IL-2, IL-5, GM-CSF and IFN- and so provide an assay to detect immunosuppressants like FK506 and anti-inflammatories such as PDE IV inhibitors.During the early discovery of novel TLR agonists for the treatment of asthma we initially showed that PHA-L is a specific human TLR4 agonist, devoid of effects on equivalent TLR4 null cells. This TLR4 agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…Because the protection conferred by ArtinM against P. brasiliensis infection depends on TLR2 activation and some lectins were previously reported to function as TLR agonists [25], we investigated if ArtinM interacted directly with TLR2. Studies showing that TLR2 needs to heterodimerize with TLR1 or TLR6 to initiate signaling and cellular activation [6], [39], [40] led us to assess the ability of ArtinM to activate HEK293A cells transfected with the TLR2 ectodomain alone, TLR2/1, TLR2/6, or TLR4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the protection conferred by ArtinM against P. brasiliensis infection depends on TLR2 activation and some lectins were previously reported to function as TLR agonists [25], we investigated if ArtinM interacted directly with TLR2. Studies showing that TLR2 needs to heterodimerize with TLR1 or TLR6 to initiate signaling and cellular activation [6], [39], [40] led us to assess the ability of ArtinM to activate HEK293A cells transfected with the TLR2 ectodomain alone, TLR2/1, TLR2/6, or TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TLR2 has N-linked oligosaccharides that are potential targets for ArtinM recognition, and other lectins have been identified as TLR agonists [25]. In the present study, we investigate the direct interaction between TLR2 and ArtinM and the dependence on carbohydrate recognition in that process.…”
Section: Introductionmentioning
confidence: 95%
“…These findings suggest that HSP70 expressed in RA synovial fluid (47), ST macrophages, and fibroblasts (33) may be a chaperone protein for TLR5 endogenous ligand(s) (48). Lectins have also been identified as novel agonists for cell surface-bound TLRs (49). On the basis of earlier investigations, there is a possibility that HSPs (33,34) and/or lectins (49) may be potential TLR5 endogenous ligands in RA joints.…”
Section: Discussionmentioning
confidence: 94%
“…When RA synovial tissue fibroblasts, macrophages and HMVECs were screened for IL-17 downstream targets, CCL5 was undetected (data not shown). Therefore, reduction in joint CCL5 concentration in anti-CXCL5 and combination therapy treatment groups may be due to reduced TNF-a levels, since CCL5 expression is known to be modulated by TNF-a in RA synovial tissue fibroblasts [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The regulating signaling pathways downstream of the mammalian TCR complex affects the members of the Src, Syk and Tec family of kinases [16] which again affects a multitude of other protein and lipid kinases, initiating the signals that determine the specific outcomes of antigen recognition [17]. Recently, Unitt & Hornigold [18] showed that phytohaemoagglutinin (PHA) also stimulated mammalian TLR2/6, 4 due to its specific carbohydrate recognition motif, indicating PHA as both an innate and adaptive immunostimulant. The mitogenic effect of PHA in fish leukocytes is well established and quantified by using [ 3 H] thymidine incorporation to measure proliferation responses [19e21].…”
Section: Introductionmentioning
confidence: 98%